CADANGAN KARBON PADA VEGETASI POHON DI PETAK 1D RPH PANCURENDANG BKPH MAJALENGKA KPH MAJALENGKA - Bimo Priyo Nusantoro (Fakultas Kehutanan Universitas Winaya Mukti, 2021)
Related to global climate stability and international issues of climate change, forests have an important role as a source of carbon emissions (source) and carbon sinks and stores (sink). One of forest ecosystem component is tree vegetation. So that, the study of trees vegetation analysis and estimating of carbon stock needs to be done as well. A total 1,05 Ha sampling Plot with 6 plots (40 x 5 m) for around 5 to 95 cm and (100 x 20 m) for around > 95 cm in four areas has been established to determine trees structure, composition, and carbon stock (above ground) in BKPH Majalengka. Enumeration of all tree species revealed that there were 12 species. The total carbon stock (above ground) was 2.086.347 Kg and avarege per Ha is 99,35 Ton.